Characterizing neuroinvasion and neuropathology of SARS-CoV-2 by using AC70 human ACE2 transgenic mice - Hsu, Jason C.; Saenkham-Huntsinger, Panatda; Huang, Pinghan; Octaviani, Cassio Pontes; Drelich, Aleksandra K.; Peng, Bi-Hung; Tseng, Chien-Te K. (Frontiers in Microbiology, 2024)
COVID-19 presents with a plethora of neurological signs and symptoms despite being characterized as a respiratory disease, including seizures, anxiety, depression, amnesia, attention deficits, and alterations in consciousness. The olfactory nerve is widely accepted as the neuroinvasive route by which the etiological agent SARS-CoV-2 enters the brain, but the trigeminal nerve is an often-overlooked additional route. Based on this consensus, we initially conducted a pilot experiment investigating the olfactory nerve route of SARS-CoV-2 neuroinvasion via intranasal inoculation in AC70 human ACE2 transgenic mice. Notably, we found that the trigeminal ganglion is an early and highly efficient site of viral replication, which then rapidly spread widely throughout the brain where neurons were primarily targeted. Despite the extensive viral infection across the brain, obvious evidence of tissue pathology including inflammatory infiltration, glial activation, and apoptotic cell deaths were not consistently observed, albeit inflammatory cytokines were significantly induced. However, the expression levels of different genes related to neuronal function, including the neurotransmitter dopamine pathway as well as synaptic function, and markers of neuronal damage were altered as compared to mock-infected mice. Our findings suggest that the trigeminal nerve may serve as a neuroinvasive route complementary to the olfactory nerve and that the ensuing neuroinvasion presented a unique neuropathological profile. This study provides insights into potential neuropathogenic mechanisms utilized by coronaviruses.